Jordan Type Inequalities for Hyperbolic Functions and Their Applications. (1st March 2015) - Yang, Zhen-Hang; Chu, Yu-Ming
Abstract : We present the best possible parameters p, q ∈ 0, ∞ such that the double inequality1 / 3 p 2 c o s h ( p x ) + 1 - 1 / 3 p 2 < s i n h ( x ) / x < 1 / 3 q 2 c o s h ( q x )   +   1   -   1 / 3 q 2 holds for allx ∈ 0, ∞ . As applications, some new inequalities for certain special function and bivariate means are found.